Upaya Perlindungan Hukum Terhadap Anak Selaku Korban Tindak Pidana Perdagangan Orang (Human Trafficking) di Indonesia - Malau, Ruben (Verdict: Journal of Law Science, 2023)
The state guarantees the protection of the rights of child victims of trafficking, which is a fundamental human right. However, child trafficking continues to occur, making it necessary to analyze the contributing factors and the efforts to protect children. The aim of this study is to examine the crime of trafficking in persons involving children, the triggering factors, and the legal protection provided for child victims of trafficking in Indonesia. This research employs a normative juridical method with a legislative approach. The findings of this study indicate that: (1) Child trafficking occurs when a minor is lured, transported, harbored, or handed over to another person for the purpose of exploitation. Several factors contribute to the persistence of child trafficking, with poverty being one of the main triggers; (2) Legal protection for children as victims of trafficking is regulated by Law No. 35 of 2014 concerning amendments to Law No. 23 of 2002 on Child Protection, along with other relevant regulations in Indonesia. However, despite these regulations, child trafficking remains prevalent and requires more comprehensive handling.